Pengaruh Inovasi Sistem Pembayaran dan Variabel Makroekonomi Terhadap Jumlah Uang Beredar di Indonesia - Nadhira Syifa; Ali Anis; Alpon Satrianto (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2019)
This study aims to analyze the long-term effects and short-term shocks of RTGS value, clearing value, electronic money value, inflation and interest rates on the money supply in Indonesia. The impacts of these shocks will be the basis for decision-making and policy-setting in achieving optimal economic growth. This study uses the ECM method to see the long-term and short-term effects of payment system innovation and macroeconomic variables on the money supply in Indonesia. The data used is time series from 2009:Q1-2017Q3 collected through documentation from relevant government agencies. In more detail, the technique used is with Error Correction Model (ECM) to analyze short-term shocks. The results obtained show that in the short term, the value of clearing, inflation, and interest rate variables cause shocks to the money supply in Indonesia. In the long run, the variable of RTGS value, the clearing value, the electronic money value, and the inflation have a significant effect on the money supply in Indonesia.